2017
DOI: 10.1016/j.ecolecon.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Payment for multiple forest benefits alters the effect of tree disease on optimal forest rotation length

Abstract: Forests deliver multiple benefits both to their owners and to wider society. However, a wave of forest pests and pathogens is threatening this worldwide. In this paper we examine the effect of disease on the optimal rotation length of a single-aged, single rotation forest when a payment for non-timber benefits, which is offered to private forest owners to partly internalise the social values of forest management, is included. Using a generalisable bioeconomic framework we show how this payment counteracts the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The following equation developed by Macpherson shows the objective function to assess the forest value that includes the timber and the non-timber incomes [10]:…”
Section: Economic Evaluation Of Korean Oak Wiltmentioning
confidence: 99%
See 1 more Smart Citation
“…The following equation developed by Macpherson shows the objective function to assess the forest value that includes the timber and the non-timber incomes [10]:…”
Section: Economic Evaluation Of Korean Oak Wiltmentioning
confidence: 99%
“…Dynamic optimization can be used to find the optimal rotation age for trees suggested by Faustmann [8] and further suggested by Hartman [9], considering wood as well as non-wood services. Macpherson et al [10] generalized the Hartman model and showed that when the payout to non-timber value is considered, the rotation age could be shortened or extended relying on the distribution of the pathogenic pests. The result was contrary to the notion that the rotation age is generally believed to decrease when forest pests occur.…”
Section: Introductionmentioning
confidence: 99%
“…Bioeconomic models have also been used to assess the effect of a pathogen on the optimal rotation length of forests (Macpherson et al, 2016, Macpherson et al, 2017). The authors adapted a classical Faustmann model to include the rate of pathogen spread (through a Susceptible-Infected epidemiological model).…”
Section: Bioeconomic Modelling Of the Effect Of Pests And Pathogens Omentioning
confidence: 99%
“…This optimal control framework showed that the optimal rotation length (the forest age at which net present value of the forest is maximised) of a plantation forest is generally shortened when the damage from disease reduces the timber benefit (Macpherson et al, 2016). When a forest manager considers both the timber and non-timber benefits, and the damage from disease reduces the timber benefit only, the optimal rotation length increases; when the damage reduces both the timber and the non-timber benefits, the optimal rotation length is reduced (Macpherson et al, 2017). …”
Section: Bioeconomic Modelling Of the Effect Of Pests And Pathogens Omentioning
confidence: 99%
See 1 more Smart Citation